Associations of self estimated workloads with musculoskeletal symptoms among hospital nurses. Issue 3 (1st March 2000) - Ando, Shoko; Ono, Yuichiro; Shimaoka, Midori; Hiruta, Shuichi; Hattori, Yoji; Hori, Fumiko; Takeuchi, Yasuhiro
Abstract : OBJECTIVES: To investigate the prevalence of neck, shoulder, and arm pain (NSAP) as well as low back pain (LBP) among hospital nurses, and to examine the association of work tasks and self estimated risk factors with NSAP and LBP. METHODS: A cross sectional study was carried out in a national university hospital in Japan. Full time registered nurses in the wards (n=314) were selected for analysis. The questionnaire was composed of items on demographic conditions, severity of workloads in actual tasks, self estimated risk factors for fatigue, and musculoskeletal pain in the previous month. Rate ratios (RRs) and 95% confidence intervals (95% CIs) were calculated by the Cox's proportional hazards model to study the association of pain with variables related to work and demographic conditions. RESULTS: The prevalences of low back, shoulder, neck, and arm pain in the previous month were 54.7%, 42.8%, 31.3%, and 18.6%, respectively. The prevalence of musculoskeletal symptoms among hospital nurses was higher than in previous studies. In the Cox's models for LBP and NSAP, there were no significant associations between musculoskeletal pain and the items related to work and demographic conditions. The RRs for LBP tended to be relatively higher for "accepting emergency patients" and some actual tasks. Some items of self estimated risk factors for fatigue tended to have relatively higher RRs for LBP and NSAP. CONCLUSIONS: It was suggested that musculoskeletal pain among hospital nurses may have associations with some actual tasks and items related to work postures, work control, and work organisation. Further studies, however, are necessary, as clear evidence of this potential association was not shown in the study.